Peculiarities of students’ experiencing a life meaning crisis - Chuyko, Halyna; Koltunovych, Tetiana; Chaplak, Yan; Zvarych, Ihor (Toruń: Wydawnictwo Adam Marszałek, 2021)
The article is devoted to the following important philosophical and psychological phenomenon: a life meaning crisis and the peculiarities of its experience in student age. This concept is considered in the context of the intersection of studies of hardiness, basic beliefs of the individual and existential fulfillment. It is stated that the process of experiencing a life meaning crisis in its severity and unexpectedness resembles an emotional state that disrupts the normal course of human life and is experienced as feelings of suffering, grief, loss, despair, danger, and its course does not depend on human efforts or desires. The study sample consisted of 78 students. The average age of respondents was 19.2 years. The existence of statistically significant inverse relationships between experiencing a life meaning crisis and hardiness, emotional fulfillment and basic personal beliefs has been empirically proven. Peculiarities of students with different levels of experiencing a life meaning crisis are determined. It was found that as the level of life meaning crisis increases, students’ dissatisfaction with what they do increases, they do not feel included in life, instead feel helpless, unwilling to take risks and actively assimilating knowledge, unable to rely on their own experience in relevant situations, which ultimately leads to internal tension in stressful situations and lack of resilience.
Keywords: sensowny kryzys życiowy; sens życia; podstawowe przekonania; witalność; spełnienie egzystencjalne